Low-grade Fibromyxoid Sarcoma With Heterotopic Bone Formation: Case Report and Review of the Literature. Issue 9 (19th October 2022) - Serinelli, Serenella; Mookerjee, Gaurav G.; Stock, Harlan; de la Roza, Gustavo; Damron, Timothy; Gitto, Lorenzo; Zaccarini, Daniel J.
Abstract : Low-grade fibromyxoid sarcoma is an uncommon soft tissue malignant neoplasm with deceptively bland histologic appearance, and a tendency for late recurrence and metastasis. Cases with significant heterotopic ossification are exceedingly rare. In the literature, only 9 cases of low-grade fibromyxoid sarcoma with bone formation proven by histopathology have been described in detail in the literature. We report the case of a 42-year-old male presenting with a 20-year history of a painless tumor in his left upper thigh. Computed tomography images showed coarse punctate central and peripheral calcifications, and the mass was resected. The tumor cells were immunohistochemically positive for MUC4, and also positive for FUS (16p11.2) gene rearrangement by fluorescence in situ hybridization. Besides, immunohistochemistry showed focal weak to moderate staining for TLE-1. At histology, heterotopic ossification was also observed. A diagnosis of low-grade fibromyxoid sarcoma (grade 1, stage T4) was rendered, and prior reports of these tumors with bone formation have not concomitantly described TLE-1 staining. This paper aims to characterize the radiologic, pathologic, and clinical features of low-grade fibromyxoid sarcoma showing heterotopic ossification reported in the literature, and further review the morphologic spectrum of this malignant neoplasm.